The road to Negan: Governance and power in The Walking Dead. Issue 3 (1st October 2018) - Howe, Andrew; Evans, Sean
In Robert Kirkman's graphic novel The Walking Dead (2003–present), a zombie apocalypse serves as the backdrop against which the survivors make the practical and moral decisions that will determine their fate. The struggle is less about combating the undead than maintaining a civilized, moral imperative and reformulating a micro-society from the ashes of previous civilization. Leadership and decisionmaking become critical in situations where the wrong choice can result in destruction. The television adaptation offers a rare glimpse into a world where some of the fundamental features of civilization – government, kinship, culture – are simultaneously and completely enveloped in chaos. In the midst of a complete breakdown of structure, power vacuums occur and are inevitably filled, most notably in the early parts of the series by Rick Grimes and Shane Walsh, friends and former law enforcement officers who model very different visions of power and governance. This article explores power structures and hierarchy in The Walking Dead from two disciplinary perspectives – historical/cultural and psychological – and focuses upon the clash of competing hierarchal structures and leadership styles that develop as the survivors band together and begin to seek out islands of safety from zombies and other humans alike. The zombie apocalypse is thus a backdrop against which to project the real story: the power dynamics within a micro-society undergoing tremendous stress, and what these dynamics indicate about the conflicted nature of power and identity.